Emerging thermal and nonthermal technologies in food processing - Srivastav, Prem Prakash; Verma, Deepak Kumar, 1986-; Patel, Ami R.; Al-Hilphy, Asaad Rehman (Burlington, ON ; Palm Bay, Florida : Apple Academic Press, 2020)
"This new volume, Emerging Thermal and Nonthermal Technologies in Food Processing, provides a comprehensive overview of thermal and nonthermal processing of food with new and innovative technologies. Recent innovations in thermal as well as nonthermal technologies, which are specifically applied for potable water and fluid foods (milk, juice, soups, etc.), are well documented for their high bioavailability of macro- and micronutrients and are very promising. This brings together valuable information on fluid and microbial characteristics and quality dynamics that facilitate the adoption of new technology for food processing. Some new technologies and methods covered include the application of microwaves in heating, drying, pasteurization, sterilization, blanching, baking, cooking, and thawing; microwave-assisted extraction of compounds; using low-electric fields; alternation of temperature and pressure of supercritical carbon dioxide; ultrasound-assisted osmotic dehydration; hydrodynamic cavitation; high-pressure processing; gamma-irradiation; and more. The nonthermal technologies discussed have been developed as an alternative to thermal processing while still meeting required safety or shelf-life demands and minimizing the effects on nutritional and quality attributes. With contributions from a broad range of leading researchers, this comprehensive volume will be a valuable reference and useful guide for students, educators, researchers, food processors, and industry personnel looking for up-to-date insights in the field. The authors believe that worldwide adoption of these novel technologies will benefit consumers in terms of enhanced food safety, labeling, nutritional security, and value-added products at reasonable costs"--
Keywords: Food industry and trade -- Technological innovations; Food -- Effect of heat on